Social adaptation level towards unstable rubber price among Malaysian rubber smallholders - Saufe, Nur Aqilah; Man, Norsida (International Organization of Scientific Research, 2017)
National Key Economic Area (NKEA) for rubber involves three (3) Entry Point Projects (EPPs) and one of the targets is to ensure sustainability of the upstream rubber industry in Malaysia. This EPP aims to increase the area of replanting and new planting of rubber by independent smallholders to 24,000 hectares. More replanting exercises can also be expected following the government’s rubber incentive to aid rubber smallholders suffering from weak commodity prices. Rubber smallholders produce 94% of the Malaysian rubber production. Nowadays, rubber smallholders need to face many challenges especially in rubber price fluctuation. The unstable prices of natural rubber could affect the income and socio-economics of the rubber smallholders. This paper employed survey data to identify smallholders’ social adaptation level towards unstable rubber price among Malaysian smallholders. 400 of respondents who are rubber smallholders in four (4) districts area (Baling, Kulim, Gua Musang and Kuala Krai) were involved in this study. The results show that 76.5% of respondents are male and the rest of 23.5% are female. The most predominant age group of the respondents are more 56 years old which are 42.0%. For the marital status of the respondents, there were 90.0% are married, 1.5% are single and 8.5% are widow and widower. 35.0% respondents went to primary schools while about 38.5% went to secondary schools. Meanwhile, only 4.0% had college/university education and 22.5% did not get any formal education. In general, the income level of smallholders is still low (68.5% less than RM1000). The main factors affecting the income of the smallholders are the current rubber price and the old age of the trees. The overall mean for social adaptation level of smallholders towards the impact of unstable rubber price is 2.501 considered as a moderate level of perception.